1987
DOI: 10.1111/j.1471-0528.1987.tb03122.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing incidence of caesarean section in the Health District of Central Manchester

Abstract: The caesarean section rate in England and Wales has practically doubled from 5.6% in 1974 to 10.6% in 1982. Because most statistical reports are based on the practice of individual hospitals and do not reflect what is occurring in a particular community, a retrospective study of the incidence of, and reasons for, caesarean section performed in residents of the geographically defined Health District of Central Manchester was carried out for 1974 and 1982. The caesarean section rate in this community increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It has been suggested that the occurrence of prolonged labour in nulliparous women could be virtually eliminated by adherence to the principles of active management (Duignan 1985), and that the incidence of caesarean section could be dramatically reduced (Philpott & Castle 1972a, b; O'Driscoll & Meagher 1986; Turner et al 1988). However, despite widespread adoption of active management regimes, trends show that caesarean section rates are rising, the greatest increase being due to failure to progress in labour (Neuhoff et al 1989; Schifrin & Cohen 1989; Kiwanuka & Moore 1987)—the problem that active management was intended to address.…”
mentioning
confidence: 99%
“…It has been suggested that the occurrence of prolonged labour in nulliparous women could be virtually eliminated by adherence to the principles of active management (Duignan 1985), and that the incidence of caesarean section could be dramatically reduced (Philpott & Castle 1972a, b; O'Driscoll & Meagher 1986; Turner et al 1988). However, despite widespread adoption of active management regimes, trends show that caesarean section rates are rising, the greatest increase being due to failure to progress in labour (Neuhoff et al 1989; Schifrin & Cohen 1989; Kiwanuka & Moore 1987)—the problem that active management was intended to address.…”
mentioning
confidence: 99%
“…The case presented highlights, as do many others, the problems experienced in obstetrics today, namely, an increasing proportion of caesarean sections being performed for failure to progress in the first stage of labour without clear evidence of cephalo‐pelvic disproportion or aberrant mechanisms (Kiwanuka et al 1987). Furthermore, many women undergoing caesarean section for failure to progress deliver normally in subsequent labours, as did this woman.…”
mentioning
confidence: 79%
“…If the membranes rupture early and there is a hind water leak, do not induce labour but manage conservatively with prophylactic antibiotics. If the baby is thought to be small, a distinction should be made between those who have IUGR and the small normal baby (Kiwanuka and Moore (1987).…”
mentioning
confidence: 99%